A new species of Ergasilus von Nordmann, 1832 (Copepoda: Cyclopoida) from the gills of a dasyatid ray, Himantura oxyrhyncha (Sauvage, 1878) from West Kalimantan, Indonesia - Boxshall, Geoffrey A. (Zootaxa, 2016)
A new species of the cyclopoid copepod genus Ergasilus von Nordmann, 1832 is described based on material collected from the gills of an elasmobranch, Himantura oxyrhyncha (Sauvage, 1878), collected in the Java Sea off the coast of West Kalimantan, Indonesia. To justify the establishment of the new species, Ergasilus kimi sp. nov., detailed comparisons are made with the 28 congeneric species that share the combination of a 3-segmented leg 1 endopod and the presence of 2 setae on the free exopodal segment of leg 5. This is the fourth report of an Ergasilus species infecting an elasmobranch and it is concluded that each represents an independent colonization event of elasmobranchs as hosts.